Photoaging and Cosmetic Result with Artificial Daylight Photodynamic Therapy Using Methyl Aminolevulinate - Rolf-Markus Szeimies; Matthias Brückner; Matthias Hoffmann; Melvin Baé; Jörg Fränken; Bernd Großmann; Uwe Paasch; Sven Quist; Berenice M. Lang; Rajeev Chavda; Wolfgang G. Philipp-Dormston (Acta Dermato-Venereologica)
Artificial daylight photodynamic therapy with methyl aminolevulinate is an effective and almost painless treatment approach for actinic keratoses. The objective of the prospective, non-interventional, multicentre study ArtLight (NCT05725213) was to gain comprehensive insights into the cosmetic effect of methyl aminolevulinate-artificial daylight photodynamic therapy in patients with actinic keratoses using different artificial daylight systems under real-world conditions. The study enrolled patients with Olsen grade 1 or 2 actinic keratoses on the face and scalp in Germany. Patients were treated with methyl aminolevulinate-artificial daylight photodynamic therapy. The cosmetic effect was assessed via photodamage parameters (global score for photoaging, mottled pigmentation, tactile roughness, telangiectasias, fine lines). Each photodamage variable was recorded on a 5-point scale (0–4). In total, 224 patients (median age: 75.0 years [range 50–91], 85.3% male, 62.5% Olsen grade 2, 55.4% treatment-naive) were treated with methyl aminolevulinate-artificial daylight photodynamic therapy. At month 3, all 5 parameters of photoaging were significantly reduced from baseline (p < 0.001). The majority of patients (81.3%) and investigators (83.6%) rated the cosmetic result as good or very good. Beyond effective eradication of actinic keratoses, field-directed methyl aminolevulinate-artificial daylight photodynamic therapy can improve photoaging symptoms, including tactile roughness, mottled pigmentation, telangiectasis, and fine lines. Thus methyl aminolevulinate-artificial daylight photodynamic therapy provides additional benefits, particularly for patients concerned with cosmetic outcomes during or after treatment.